2008
DOI: 10.1007/s00381-008-0650-4
|View full text |Cite
|
Sign up to set email alerts
|

Phrenic nerve neurotization utilizing the spinal accessory nerve: technical note with potential application in patients with high cervical quadriplegia

Abstract: To our knowledge, using the SAN for neurotization to the phrenic nerve for potential use in patients with spinal cord injury has not been previously explored. Following clinical trials, these data may provide a mechanism for self stimulation of the diaphragm and obviate phrenic nerve pacing in patients with high cervical quadriplegia. Our study found that such a maneuver is technically feasible in the cadaver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The spinal accessory nerve (SAN) has been shown to be a possible donor nerve for anastomosis with the PN to restore physiological respiration. 9,28,29,31 However, the SAN does not have spontaneous discharge, and an external electronic pacing has to be provided. Spontaneous discharge from a donor nerve is important for restoration of spontaneous respiratory function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spinal accessory nerve (SAN) has been shown to be a possible donor nerve for anastomosis with the PN to restore physiological respiration. 9,28,29,31 However, the SAN does not have spontaneous discharge, and an external electronic pacing has to be provided. Spontaneous discharge from a donor nerve is important for restoration of spontaneous respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal accessory nerve (SAN) and PN anastomosis has been shown to be a possible way to restore the respiratory movement of the diaphragm. 9,28,29,31 Our previous study showed that vagus nerve (VN) to PN anastomosis could partially improve respiratory function in rabbits that had been subjected to unilateral PN transection. 30 Nevertheless, there are drawbacks to using the VN for anastomosis to the PN, even though the VN contains some fibers that produce efferent discharges synchronous with the PN.…”
mentioning
confidence: 99%
“…The posterior approach could even allow the accessory nerve to be harvested for use in neurotization procedures involving the radial nerve branches to the triceps brachii muscle, and the axillary nerve at its exit from the quadrangular space (Vathana et al, ; Tubbs et al, a). A recent cadaveric feasibility study by Tubbs et al () showed that the accessory nerve would be feasible for use in neurotization of the phrenic nerve in patients with high cervical quadriplegia (Tubbs et al, ). Additionally, Tubbs et al () have shown that the accessory nerve in the posterior cervical triangle can be lengthening in order to use it for neurotization procedures more distally.…”
Section: Surgerymentioning
confidence: 99%
“…Restoration of the diaphragm by anastomosing the SAN with the phrenic nerve has been reported in animal and cadaver studies. 9,12 In the animal models, the transferred SAN could effectively pace the diaphragm; however, no clinical application has been reported. Based on our case study, the procedure led to satisfactory results: 6 months after the operation, partial improvements in the motion of the diaphragm were observed, and the patient's lung function, especially the tidal volume, could fulfill the demands of his daily life.…”
Section: Clinical Effectsmentioning
confidence: 99%